#URGENTE
1)Resolver, em R, a equação (log de x na base 2)^2-log de x^3 na base 2+2=0.
2)Resolver, em R, a equação 4^x-2^x+2+3=0.
Soluções para a tarefa
Respondido por
0
1) (
)² - ![log_{2} x^{3} log_{2} x^{3}](https://tex.z-dn.net/?f=+log_%7B2%7D++x%5E%7B3%7D+)
= 0
![(log_{2}x) ^{2} - 3. log_{2}x+2 = 0 (log_{2}x) ^{2} - 3. log_{2}x+2 = 0](https://tex.z-dn.net/?f=++%28log_%7B2%7Dx%29+%5E%7B2%7D+-+3.+log_%7B2%7Dx%2B2+%3D+0+)
Sendo
, temos :
a²-3a+2 = 0
Δ = (-3)²-4.1.2
Δ = 9-8
Δ = 1
a' = 3+√1 / 2 = 3+1 / 2 = 4/2 = 2
a'' = 3-√1 / 2 = 3-1 /2 = 2/2 = 1
Então :
⇒ x = 2² = 4
ou
⇒ x = 2¹ = 2
2) 4ˣ - 2ˣ⁺² + 3 = 0
(2²)ˣ - 2ˣ.2² + 3 = 0
(2ˣ)² - 4.2ˣ + 3 = 0
Sendo 2ˣ = k , temos :
k²-4k+3 = 0
Δ = (-4)²-4.1.3
Δ = 16 - 12
Δ = 4
k' = 4+√4 / 2 = 4+2 / 2 = 6/2 = 3
k'' = 4-√4 / 2 = 4-2 / 2 = 2/2 = 1
Então :
2ˣ = 3
log2ˣ = log3
x.log2 = log3
x = log3/log2
ou
2ˣ = 1
2ˣ = 2⁰
x = 0
Sendo
a²-3a+2 = 0
Δ = (-3)²-4.1.2
Δ = 9-8
Δ = 1
a' = 3+√1 / 2 = 3+1 / 2 = 4/2 = 2
a'' = 3-√1 / 2 = 3-1 /2 = 2/2 = 1
Então :
ou
2) 4ˣ - 2ˣ⁺² + 3 = 0
(2²)ˣ - 2ˣ.2² + 3 = 0
(2ˣ)² - 4.2ˣ + 3 = 0
Sendo 2ˣ = k , temos :
k²-4k+3 = 0
Δ = (-4)²-4.1.3
Δ = 16 - 12
Δ = 4
k' = 4+√4 / 2 = 4+2 / 2 = 6/2 = 3
k'' = 4-√4 / 2 = 4-2 / 2 = 2/2 = 1
Então :
2ˣ = 3
log2ˣ = log3
x.log2 = log3
x = log3/log2
ou
2ˣ = 1
2ˣ = 2⁰
x = 0
vitoriaata8:
Muito obrigada
Perguntas interessantes
Ed. Física,
11 meses atrás
Informática,
11 meses atrás
Inglês,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás